Promotion of Pro-Apoptotic Signals by Lysosomal Photodamage - Kessel, David (Photochem Photobiol, 2015)
We previously reported that low level lysosomal photodamage enhanced the efficacy of subsequent mitochondrial photodamage, resulting in a substantial promotion of apoptotic cell death. We now extend our analysis of the sequential PDT protocol to include two additional lysosomal-targeting photosensitizers. These agents, because of enhanced permeability, are more potent than the agent (N-aspartyl chlorin E6, NPe6) used in the initial study. Addition of the cell-permeable cysteine protease inhibitor E-64d and calcium chelator BAPTA-AM almost completely suppressed sequential PDT-induced loss of mitochondrial membrane potential, activation of procaspases-3 and -7 and loss of colony formation. These inhibitors did not, however, suppress the pro-apoptotic effect of a BH3 mimetic or mitochondrial photodamage. Knockdowns of ATG7 or ATG5, proteins normally associated with autophagy, suppressed photodamage induced by the sequential PDT protocol. These effects appear to be independent of the autophagic process since pharmacological inhibition of autophagy offered no such protection. Effects of ATG7 and ATG5 knockdown may reflect the role that ATG7 plays in regulating lysosome permeability, and the likelihood that a proteolytic fragment of ATG5 amplifies mitochondrial pro-apoptotic processes. Our results suggest that low-dose photodamage that sequentially targets lysosomes and mitochondria may offer significant advantages over the use of single photosensitizers.